Peran Pegadaian Syariah dalam Mendorong Kesejahteraan Sosial Masyarakat Melalui Program Corporate Social Responsibility (CSR) - Azizah Anna Sahra; Fajar Rizky Lubis; Anwar Yusuf; Ira Hairani; Siti Wulandari; Rosalena; Pahrurrozi Pane; Nur Indah Hidayah; Suci Indah Pulungan; Nurul Irawan Rangkuti; Erpiana Siregar (PT. Willy Print Art, 2025)
Corporate Social Responsibility (CSR) is a concept that has developed since post-World War II, focusing on the social and environmental impacts of corporate activities. From an Islamic perspective, CSR not only functions as a legal obligation, but also as a form of contribution to social welfare based on spiritual values. This study examines the implementation of CSR based on sharia principles carried out by Pegadaian Syariah, with the aim of improving the welfare of the surrounding community. The method used is a collaborative participatory approach between the service team, Pegadaian Syariah, and the community. The results of the study show that the CSR program carried out not only improves sharia financial literacy and economic empowerment, but also strengthens social relations between residents. Programs such as entrepreneurship training, business capital assistance, and sharia financial education have succeeded in improving the standard of living of the community and strengthening the role of Pegadaian Syariah in social development. This success shows the great potential of CSR based on religious values ​​and local wisdom for sustainable development.